- Thread starter
- #1

- Thread starter gazparkin
- Start date

- Thread starter
- #1

- Thread starter
- #2

Sorry, there's another one that I'm stuck on too. Really interested to understand the working out on this.Hi,

Could someone help me with this question:

2x – 1 = 9 – 3x

Thank you in advance!!!

4(3b-1)+6=5(2b+4)

Step 1: Get all the x's on one side: Subtract 2x on both sides:Hi,

Could someone help me with this question:

2x – 1 = 9 – 3x

Thank you in advance!!!

2x - 1 - 2x = 9 - 3x - 2x

-1 = 9 - 5x

Now do the same with the numbers. Can you finish?

-Dan

- - - Updated - - -

Expand the parentheses:Sorry, there's another one that I'm stuck on too. Really interested to understand the working out on this.

4(3b-1)+6=5(2b+4)

4(3b - 1) + 6 = 5(2b + 4)

\(\displaystyle 4 \cdot 3b + 4 \cdot (-1) + 6 = 5 \cdot 2b + 5 \cdot 4\)

Now combine terms:

12b - 4 + 6 = 10b + 20

12b + 2 = 10b + 20

Now it's like your first problem. Can you finish?

-Dan

- Thread starter
- #4

Step 1: Get all the x's on one side: Subtract 2x on both sides:

2x - 1 - 2x = 9 - 3x - 2x

-1 = 9 - 5x

Now do the same with the numbers. Can you finish?

-Dan

- - - Updated - - -

Expand the parentheses:

4(3b - 1) + 6 = 5(2b + 4)

\(\displaystyle 4 \cdot 3b + 4 \cdot (-1) + 6 = 5 \cdot 2b + 5 \cdot 4\)

Now combine terms:

12b - 4 + 6 = 10b + 20

12b + 2 = 10b + 20

Now it's like your first problem. Can you finish?

-Dan

Thanks Dan - makes this really clear. The first one I get x=4 and the 2nd one I get b=9.

The second one is okay. Let's take another look at the first one. I left off withThanks Dan - makes this really clear. The first one I get x=4 and the 2nd one I get b=9.

-1 = 9 - 5x

Now get the numbers:

-1 - 9 = 9 - 5x - 9

\(\displaystyle \dfrac{-10}{-5} = \dfrac{-5x}{-5} \)

2 = x

-Dan